Bull Gore Injury of the Vagina - Kulkarni, Maitri Raghavendra (JCDR Research and Publications (P) Limited, 2013)
Although an obstetrically related trauma is the most common cause of the injuries to the female genital tract, non obstetric causes also lead to a significant number of vaginal and vulval injuries. We present 2 cases of vaginal injury, due to bull goring, one of which was associated with massive vulval haematoma. The 2 cases presented in a span of 2 months, in a rural medical college in South India. Both of them were managed surgically, following an initial haemodynamic resuscitation. They also required blood transfusions and an antibiotic prophylaxis. The postoperative period was uneventful.